Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How can I find a equivalent conditions for the following inequality $$ 0\leq x+\frac{1}{2}x(1-x)a\leq 1? $$

This is from a numerical analysis book, Finite-Volume Methods For Hyperbolic Problems. I have no idea why this can be equivalent to $$ 0\leq x\leq 1\qquad\text{and}~|a|\leq 2. $$

How can one come up with such conditions?

share|cite|improve this question
I don't think they are equivalent. But the second one should imply the first one. The problem is that how can one come up with such condition? – Jack Nov 9 '11 at 16:32
Let $f_a(x)$ be the function you wish to bound. To show $0 \leq f_a(x)$ and $f_a(x) -1 \leq 0$ by hand, just note that $f_a(x)$ (and hence $f_a(x) - 1$) are quadratic functions which open downwards. So finding such conditions really amounts to finding $x$-intercepts of quadratics. – JavaMan Nov 9 '11 at 17:11
@JavaMan Not necessarily "opening downwards" -- if $a<0$. – pharmine Nov 9 '11 at 17:26
They are not equivalent: take $x=\frac{4}{3}$, $a=3$. – Arturo Magidin Nov 9 '11 at 19:32
up vote 2 down vote accepted

The inequalities are not equivalent. The inequality above holds if $a=3$ and $x=\frac{4}{3}$: $$x + \frac{1}{2}x(1-x)a = \frac{4}{3} + \frac{1}{2}\left(\frac{4}{3}\right)\left(-\frac{1}{3}\right)(3) = \frac{4}{3} - \frac{2}{3} = \frac{2}{3},$$ but this clearly does not satisfy $0\leq x \leq 1$, $|a|\lt 2$.

Here's how I found the counterexample.

If $a=0$, then the inequality is equivalent to $0\leq x \leq 1$.

If $a\neq 0$, let's divide the inequality into two quadratic inequalities: $$0\leq x + \frac{1}{2}x(1-x)a \leq 1.$$

Consider first $$ 0 \leq x + \frac{1}{2}x(1-x)a = x\left(\left(1+\frac{a}{2}\right) - \frac{a}{2}x\right).$$

The product is nonnegative if and only if we have both $x\leq 0$ and $1+\frac{a}{2} \leq \frac{a}{2}x$; or $x\geq 0$ and $1 + \frac{a}{2}\geq \frac{a}{2}x$.

If $x\geq 0$, then we need $1+\frac{a}{2}\geq \frac{a}{2}x$.

  • If $a\gt 0$, then this is equivalent to $\frac{2}{a}+1\geq x$, so we need $0\leq x \leq 1+\frac{2}{a}$.
  • If $a\lt 0$, then this is equivalent to $\frac{2}{a}+1\leq x$; if $-2\leq a \lt 0$, then we just need $x\geq 0$. If $a\leq -2$, then we need $1+\frac{2}{a}\leq x$.

If $x\leq 0$, then we need $1 + \frac{a}{2}\leq \frac{a}{2}x$.

  • If $a\gt 0$, then this is equivalent to $\frac{2}{a}+1\leq x$, which is impossible if $x\leq 0$.
  • If $a\lt 0$, then we need $\frac{2}{a}+1\geq x$. If $a\leq -2$, then $1+\frac{2}{a}\geq 0\geq x$, so this holds. If $-2\leq a\lt 0$, then we need $x\leq 1+\frac{2}{a}$.

In summary:

If $a\neq 0$, then the left inequality holds if and only if one of the following happens:

  • $a\gt 0$ and $0\leq x \leq 1+\frac{2}{a}$; or
  • $-2\leq a \lt 0$ and $x\geq 0$; or
  • $-2\leq a\lt 0$ and $x\leq 1+\frac{2}{a}$; or
  • $a\leq -2$ and $1+\frac{2}{a}\leq x$; or
  • $a\leq -2$ and $x\leq 0$.

Now look at the right hand inequality $$\left(1+\frac{a}{2}\right)x - \frac{a}{2}x^2 \leq 1$$ which is equivalent to $$ax^2 - (2+a)x + 2\geq 0.$$ The two roots of this equation are $$\frac{2+a+|a-2|}{2a}\quad\text{and}\quad \frac{2+a-|a-2|}{2a};$$ Depending on the sign of $a-2$, one of the roots is $1$, the other root is $\frac{2}{a}$.

If $a\gt 0$, then the inequality is equivalent to not being between the two roots. If $a\lt 0$, then the inequality is equivalent to being between the two roots.


Case 1. $a\leq -2$. We need either $x\leq 0$ and between $1$ and $\frac{2}{a}$; or $x\geq 1+\frac{2}{a}$ and between $1$ and $\frac{2}{a}$. So we must have either $\frac{2}{a}\leq x \leq 0$; or $1+\frac{2}{a}\leq x\leq 1$.

Case 2. $-2\leq a \lt 0$. Either $x\geq 0$ and between $\frac{2}{a}$ and $1$; or $x\leq 1 + \frac{2}{a}$ and between $1$ and $\frac{2}{a}$. That means, if $-2\leq a \lt 0$, we need either $0\leq x \leq 1$, or $\frac{2}{a}\leq x \leq 1+\frac{2}{a}$.

Case 3. $0\lt a\leq 2$. We need $0\leq x \leq 1+\frac{2}{a}$, and $x$ not between $1$ and $\frac{2}{a}$. This means we need $0\leq x \leq 1$ or $\frac{2}{a}\leq x \leq 1+\frac{2}{a}$.

Case 4. $2\leq a$. We need $0 \leq x \leq 1 + \frac{2}{a}$, and $x$ not between $\frac{2}{a}$ and $1$. This means we need $0\leq x \leq \frac{2}{a}$ or $1\leq x \leq 1 + \frac{2}{a}$. This is where the counterexample above came from.

In summary:

The inequality $$0 \leq x + \frac{1}{2}x(1-x)a\leq 1$$ holds if and only if:

  • $a=0$ and $0\leq x \leq 1$; or
  • $a\leq -2$ and $x\leq \frac{2}{a}$; or
  • $a\leq -2$ and $1+\frac{2}{a}\leq x \leq 1$; or
  • $-2\leq a \lt 0$ and $0\leq x \leq 1$; or
  • $-2\leq a \lt 0$ and $\frac{2}{a}\leq x \leq 1+\frac{2}{a}$; or
  • $0\lt a \leq 2$ and $0\leq x \leq 1$; or
  • $0\lt a\leq 2$, and $\frac{2}{a}\leq x \leq 1+\frac{2}{a}$; or
  • $2\leq a$ and $0\leq x\leq \frac{2}{a}$; or
  • $2\leq a$ and $1\leq x \leq 1+\frac{2}{a}$.

And I hope I didn't mess up the cases... but the example above, at least, is correct.

From this, we can deduce pharmine's result; for the inequality to hold for all $x$ with $0\leq x \leq 1$, we need either $a=0$, $-2\leq a\lt 0$, or $0\lt a\leq 2$. In all other cases, some values on $[0,1]$ will not satisfy the inequality.

share|cite|improve this answer
Hmmm... I'm somewhat worried by the fact that I cannot seem to derive pharmine's statement from this. I need to double check it. – Arturo Magidin Nov 9 '11 at 21:02
Aha! Found the error. Fixing it. – Arturo Magidin Nov 9 '11 at 21:45
For those who check the history: (i) I forgot to take into account the sign of $a$ when considering the conditions for the inequality involving the quadratic to hold; and (ii) I missed some values when $a\gt 0$ that do not lie between the roots but are positive anyway. – Arturo Magidin Nov 9 '11 at 21:59
Thanks a lot for your elaboration. – Jack Nov 15 '11 at 1:41

We can show that the condition for the inequality $0\le x+\frac12x(1-x)a\le 1$ to hold for all $0\le x\le 1$ is $|a|\le 2$.

Proof. Let $f(x)=x+\frac12x(1-x)a$. The inequality holds for $a=0$; we assume $a\ne 0$ below. Note that $f(x)=-\frac12a\left(x-\frac{a+2}{2a}\right)^2+\frac{(a+2)^2}{8a}$ is a quadratic function of $x$, and $f(0)=0$, $f(1)=1$.

(i) If $0<\frac{a+2}{2a}<1$, that is, if $|a|>2$, the above condition is equivalent to $0\le f(\frac{a+2}{2a})\le 1$. This does not hold because $f(\frac{a+2}{2a})=\frac{(a+2)^2}{8a}$ is smaller than $0$ (if $a<-2$) or larger than $1$ (if $a>2$).

(ii) If $\frac{a+2}{2a}\le 0$ or $\frac{a+2}{2a}\ge 1$, that is, if $|a|\le 2$, the above condition is automatically satisfied. ($f(x)$ is monotone increasing in $[0,1]$.)

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.